Comprehensive biocompatibility profiling of human pancreas-derived biomaterial - Asthana, Amish; Gallego, Amanda; Perrier, Quentin; Lozano, Tamara; Byers, Lori N.; Ho-Heo, Jun; Jeong, Wonwoo; Tamburrini, Riccardo; Rengaraj, Arunkumar; Chaimov, Deborah; Tomei, Alice; Fraker, Christopher A.; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThe importance of the extracellular matrix (ECM) to pancreatic islets has been clearly demonstrated, as isolated islets grown in culture or transplanted, quickly lose viability and function after their matrix associations have been stripped away during the isolation process. Therefore, recapitulating the islet niche is a critical objective to move the field of islet transplantation forward.MethodsAs a first step to recreating the islet microenvironment, we have recently developed a detergent-free decellularization method to obtain a decellularized solubilized ECM (dsECM) powder from human pancreas. We have also shown that this gentler method (compared to traditional detergent-based methods) allows for thorough preservation of the molecular fingerprint of the innate organ. Furthermore, incorporation of dsECM in alginate-microencapsulated human islets, showed a significant increase in insulin secretion, compared to both free and alginate-only encapsulated islets. However, it is also essential to test the interaction of dsECM with multiple cell types to establish its safety for transplantation.Results and discussionHerein, we present a comprehensive in vitro evaluation of the cytotoxicity, hemocompatibility and immunocompatibility of dsECM to establish a concentration range where it deemed safe and biocompatible. Furthermore, dsECM-based bioinks were coaxially bioprinted and the resulting construct's biocompatibility and vascularization potential were also evaluated in vivo.